"It's worth it"1 practitioner research as a tool of professional learning: starting points, conclusions and benefits from the perspective of teacher-students. Issue 4 (7th August 2020) - Heissenberger, Katharina; Matischek-Jauk, Marlies
ABSTRACT: The current study focuses on the concept PPS-PR (Personalized Professionalization in Pedagogical Fields through Practitioner Research), an approach that integrates practitioner research projects during internships. A central aim is to encourage teacher students´ professional learning (Bachelor of Primary Education). 312 Austrian teacher students carried out practitioner research projects and were invited to participate in an online survey at the end of the semester. The results show that the majority of respondents choose research topics predominantly related to the fields of methodical competences (e.g. classroom management strategies) and report consistent conclusions and long term benefits. The findings indicate that professional learning of teacher students can be supported by the PPS-PR concept. Therefore, practitioner research can be seen as a tool for developing competences that are stable and can furthermore be transferred to other situational contexts.